Goal scoring in women`s ice hockey reflecting on scoring recommendations - Pyeongchang Olympics & Finnish playoffs 2018 - Mertanen, T. (Haaga-Helia University of Applied Science, 2019)
The purpose of this case study was to determine how do women in top level score goals re-flecting on scoring recommendations. The other purpose was to compare if there are differ-ences in goal scoring between women`s ice hockey in the international level (Olympics) and national level (Finnish Playoffs). Also men`s ice hockey and goals scored by Canada and USA were compared with the results.